2013
DOI: 10.1080/17439760.2013.807354
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy violations and the search for meaning among breast cancer survivors

Abstract: A number of theoretical perspectives suggest that expectancy violations (EVs) threaten a person’s sense of meaning and prompt efforts to reinstate meaning. Yet, little to no research has explicitly examined whether EVs predict actual efforts to search for meaning. The current research redresses this gap in the literature among a sample of breast cancer survivors. The results revealed that EVs, but not life satisfaction, positively predicted the search for meaning. By comparison, the presence of meaning was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
6
0
5
Order By: Relevance
“…In the oncologic context, PIL is associated with wellbeing in general, as well as with promotion of quality of life in patients . Thus, oncologic patients who find PIL also reveal SWL . Fegg et al found similar interesting results to those obtained in this investigation, that is, that the oncologic patient, compared with the general population, found meaning in different areas of life, feeling greater satisfaction in those areas.…”
Section: Discussionsupporting
confidence: 79%
“…In the oncologic context, PIL is associated with wellbeing in general, as well as with promotion of quality of life in patients . Thus, oncologic patients who find PIL also reveal SWL . Fegg et al found similar interesting results to those obtained in this investigation, that is, that the oncologic patient, compared with the general population, found meaning in different areas of life, feeling greater satisfaction in those areas.…”
Section: Discussionsupporting
confidence: 79%
“…En psicooncología, el significado tiene cada vez más importancia, siendo una necesidad relatada por los pacientes que solicitaren apoyo para descubrir el significado en la vida (Moadel et al, 1999). En este sentido, el diagnóstico o el padecer un cáncer parece ser impulsor para la búsqueda de significado en la vida (Schlegel, Manning, & Bettencourt, 2013). La tensión revolucionaria o el sufrimiento existencial (Frankl, 1990) lleva el enfermo a evaluar su vida, a sí mismo y a su biografía y simultáneamente a procurar un sentido en su vida y en la enfermedad.…”
Section: Significado Y Salud-enfermedadunclassified
“…Adicionalmente, los cambios positivos que surgen de este crecimiento aumentan la SCV (Park & Blank, 2012). En este sentido, los enfermos oncológicos que consiguen encontrar significado en la vida revelan paralelamente SCV (Schlegel et al, 2013).…”
Section: Significado Y Salud-enfermedadunclassified
See 2 more Smart Citations